Cost- effectiveness of surgical treatments compared with early structured physiotherapy in secondary care for adults with primary frozen shoulder. (2021) - Corbacho, B.; Brealey, S.; Keding, A.; Richardson, G.; Torgerson, D.; Hewitt, C.; McDaid, C.; Rangan, A.
No abstract available